Exploring English grammar major students' attitudes towards and expectations for teachers' classroom activities at Bien Hoa Specialized High school, Ha Nam - Trần, Thị Thu Hiền (University of Languages and International Studies, 2017)
The first part, Introduction, provides all the information about the rationale, aims, scope, significance and format of the study. Research questions and methodology are also identified in this part. The second part, Development, consists of four chapters. The first chapter, Theoretical Background, reviews relevant literatures. In the next chapter, The study, the setting, subjects, instruments and data analysis process of the study is presented. The third chapter is devoted to a detailed description of Data analysis and discussion. And the last chapter, namely Recommendations for better language teaching at English major classes in the school, puts forward some recommendations for better teaching at English major classes of the school. The last part, Conclusion, presents not only a summary but also some limitations of the research and gives some suggestions for further study.